La tragedia de los comunes en la competencia vertical entre jurisdicciones (2009)
The benefits of the institutional competition are reached under certain norms that prevent the violation of rights and the depredation of the resources. The horizontal competition can take the form of violent aggression between jurisdictions (war) or that of cooperation and commerce. Its impact can be “a negative“ if substrae governments resources benevolentes compromised with the general well-being of the community, but “positives“ if they are considered to be another way of controlling the Leviathan. The vertical competition shows the same potential "positive" control panel and the same need for certain rules to fulfill this role. They are similar to the strict definition of the right of property that solves the “tragedy of the common property”. Of another form it can create a situation where the taxpayers are smart for different levels of fiscal authority as it shows the Argentine case